2013
DOI: 10.1111/mpp.12030
|View full text |Cite
|
Sign up to set email alerts
|

The noncanonical type III secretion system of Xanthomonas translucens pv. graminis is essential for forage grass infection

Abstract: Xanthomonas translucens pv. graminis (Xtg) is a gammaproteobacterium that causes bacterial wilt on a wide range of forage grasses. To gain insight into the host-pathogen interaction and to identify the virulence factors of Xtg, we compared a draft genome sequence of one isolate (Xtg29) with other Xanthomonas spp. with sequenced genomes. The type III secretion system (T3SS) encoding a protein transport system for type III effector (T3E) proteins represents one of the most important virulence factors of Xanthomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 91 publications
(144 reference statements)
6
75
0
2
Order By: Relevance
“…Genome data based on sequencing of single paired-end libraries only, revealed 284 to 296 scaffolds, while the combination with mate-pair sequencing data, as applied for Xtg29, reduced the number of scaffolds to three. In contrast, a previous Xtg29 assembly had 788 contigs (> 500 bp) and 12 scaffolds upon sequencing with the 454 FLX System [12]. De novo annotation of the 454 assembly by using the same strategy as applied in the present study, revealed 3619 predicted coding sequences (CDS) while 3543 CDS were identified for the Illumina MiSeq-based assembly of the re-sequenced Xtg29 genome (Additional file 2: Table S2).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Genome data based on sequencing of single paired-end libraries only, revealed 284 to 296 scaffolds, while the combination with mate-pair sequencing data, as applied for Xtg29, reduced the number of scaffolds to three. In contrast, a previous Xtg29 assembly had 788 contigs (> 500 bp) and 12 scaffolds upon sequencing with the 454 FLX System [12]. De novo annotation of the 454 assembly by using the same strategy as applied in the present study, revealed 3619 predicted coding sequences (CDS) while 3543 CDS were identified for the Illumina MiSeq-based assembly of the re-sequenced Xtg29 genome (Additional file 2: Table S2).…”
Section: Resultsmentioning
confidence: 82%
“…In view of the sequencing costs, homopolymer resolution, and observed GC bias in library preparations [22, 23], we decided to apply the Illumina MiSeq System by sequencing (2 × 250 bp) paired-end libraries constructed with the TrueSeq DNA LT Sample Prep Kit (Illumina Inc., San Diego, United States). The Swiss strain Xtg29, which has previously been sequenced by applying the Roche 454 Genome Sequencer FLX System [12], was re-sequenced in order to prevent bias in comparative genome analysis due to deviating sequencing strategies. Genome assembly of Xtg29 was moreover facilitated by (2 × 250 bp) sequencing of an additional 8 kb mate-pair library on an Illumina MiSeq System (Illumina Inc., San Diego, United States).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Illumina reads were mapped with the Burrows–Wheeler aligner (6) onto the contig to obtain the consensus sequence of a circular chromosome of 4,715,357 bp with an average coverage of 223× and a G+C content of 67.7%. Automated genome annotation carried out by means of the GenDB platform (7) with the Prodigal gene prediction software (8) revealed 3,736 protein-coding genes, 54 tRNAs, and two rRNA operons.…”
Section: Genome Announcementmentioning
confidence: 99%